Teaching the Rule of Product using Nature Tourism Routes - Putra, Aan; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Susanti, Elly; Nusantara, Duano Sapta; Laswadi, Laswadi (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2023)
A tourism route is a sequence of tourist attractions visited. Students are familiar with tour activities and often plan tourism routes to visit several tourist attractions. Students' experience and knowledge about tourism routes can be used as a context for teaching the rule of product. Therefore, this research aims to design a learning trajectory for the rule of product using the Indonesian Realistic Mathematics Education (PMRI) approach in the Kerinci nature tourism route context. The research method used is design research with a validation study type, which consists of three stages: preparation and design, teaching experiment, and retrospective analysis. The subjects involved in this research were 11 third-semester mathematics education students at a university in Jambi, Indonesia. The instruments include learning video recordings, student work results, field notes, and test sheets. The research results show that learning trajectories designed in the context of tourism routes can help students discover, understand, and use the rule of product in solving relevant mathematical problems. The learning tracjectory consists of four activities: making a list of Kerinci tourist attractions, determining the location of several tourist attractions on a sketch map, arranging tourist attractions in tourism routes, and solving problems regarding possible tourism routes. This research shows that the designed learning trajectory is vital in helping students discover and understand the rule of product and apply them to solving relevant problems.